Women to the Front: Power, Agency, and Devotion in New Religious Movements - (:unkn) unknown (My University, 2022)
Women’s roles in new religious movements have long been minimized in scholarship and popular media, with few exceptions. The dissertation looks at the new religions of the Branch Davidians in Waco, Texas; Peoples Temple in Jonestown, Guyana; and the Rajneesh movement in Rajneeshpuram, Oregon. In these three communities, women dedicated themselves to the movement itself, the charismatic male leader, or, as most often was the case, somewhere on a spectrum between the two extremes. The dissertation also addresses the power of women in these movements as leaders and influential figures. Agency, the study of freewill and autonomy of the women in these new religions, is explored, including who joined and why they chose to stay. Finally, this dissertation analyzes the ways in which women specifically demonstrated their devotion to these new religious movements and charismatic leaders.
Keywords: cult; Jonestown; new religious movement; Rajneeshpuram; Waco; women